Targeting VGLUT2 in Mature Dopamine Neurons Decreases Mesoaccumbal Glutamatergic Transmission and Identifies a Role for Glutamate Co-release in Synaptic Plasticity by Increasing Baseline AMPA/NMDA Ratio - Papathanou, Maria; Creed, Meaghan; Dorst, Matthijs C.; Bimpisidis, Zisis; Dumas, Sylvie; Pettersson, Hanna; Bellone, Camilla; Silberberg, Gilad; Lüscher, Christian; Wallén-Mackenzie, Åsa (Frontiers in Neural Circuits, 2018)
Expression of the Vglut2/Slc17a6 gene encoding the Vesicular glutamate transporter 2 (VGLUT2) in midbrain dopamine neurons enables these neurons to co-release glutamate in the nucleus accumbens (NAc), a feature of putative importance to drug addiction. For example, it has been shown that conditional deletion of Vglut2 gene expression within developing dopamine neurons in mice causes altered locomotor sensitization to addictive drugs, such as amphetamine and cocaine, in adulthood. Alterations in dopamine neurotransmission in the mesoaccumbal pathway has been proposed to contribute to these behavioral alterations but the underlying molecular mechanism remains largely elusive. Repeated exposure to cocaine is known to cause lasting adaptations of excitatory synaptic transmission onto medium spiny neurons (MSNs) in the NAc, but the putative contribution of VGLUT2-mediated glutamate co-release from the mesoaccumbal projection has never been investigated. In this study, we implemented a tamoxifen-inducible Cre-LoxP strategy to selectively probe VGLUT2 in mature dopamine neurons of adult mice. Optogenetics-coupled patch-clamp analysis in the NAc demonstrated a significant reduction of glutamatergic neurotransmission, whilst behavioral analysis revealed a normal locomotor sensitization to amphetamine and cocaine. When investigating if the reduced level of glutamate co-release from dopamine neurons caused a detectable post-synaptic effect on MSNs, patch clamp analysis identified an enhanced baseline AMPA/NMDA ratio in dopamine receptor subtype 1 (DRD1)-expressing accumbal MSNs which occluded the effect of cocaine on synaptic transmission. We conclude that VGLUT2 in mature dopamine neurons actively contributes to glutamatergic neurotransmission in the NAc, a finding which for the first time highlights VGLUT2-mediated glutamate co-release in the complex mechanisms of synaptic plasticity in drug addiction.